2012
DOI: 10.1111/j.1755-3768.2012.02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Macular thickness predictive of visual field sensitivity in ischaemic optic neuropathy

Abstract: . Purpose:  To investigate the ability of optical coherence tomography (OCT) parameters of macular thickness (MT) and peripapillary retinal nerve fibre layer (RNFL) thickness to differentiate eyes with nonarteritic anterior ischaemic optic neuropathy (NAION) from uninvolved eyes and to identify the relationship between macular and RNFL parameters and visual field sensitivity (VFS). Methods:  Thirty patients with unilateral NAION participated in a prospective observational cross‐sectional study. Patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…2 Also, it has been reported that the decrease in macular thickness is caused by the decrease in the ganglion cell complex (GCC) because there is ganglion cell loss in patients with chronic NAION. 13,28 As the ganglion cells die as a result of the NAION, the GCC and macular thicknesses become thinner. GCC is composed of three layers in the inner part of the retina, including the retinal nerve fibre layer, the ganglion cell layer, and the inner-plexiform layer.…”
Section: Discussionmentioning
confidence: 99%
“…2 Also, it has been reported that the decrease in macular thickness is caused by the decrease in the ganglion cell complex (GCC) because there is ganglion cell loss in patients with chronic NAION. 13,28 As the ganglion cells die as a result of the NAION, the GCC and macular thicknesses become thinner. GCC is composed of three layers in the inner part of the retina, including the retinal nerve fibre layer, the ganglion cell layer, and the inner-plexiform layer.…”
Section: Discussionmentioning
confidence: 99%
“…Papchenko et al 7 showed that both macular thickness and volume parameters are correlated with visual sensitivity, using Stratus OCT and Humphrey automated perimetry in NAION. Aggarwal et al 4 stated that pRNFL and macular GCL losses correlated well with VF losses in both magnitude and location.…”
Section: Discussionmentioning
confidence: 99%
“…This is different from the previous studies. 4,7 Generally, early superior disc oedema accompanies inferior field defect with decreased superior GCL þ IPL thickness. In our case, a disagreement between the area of early increased disc oedema and GCL þ IPL thickness decrease was observed.…”
Section: Discussionmentioning
confidence: 99%
“…5 Defects in the RNFLT have been observed in NAION. [6][7][8][9][10] The RGC layer is more than 1 cell layer thick at the macula (cell density up to 4-6 cell bodies thick); therefore, it was proposed that loss of retinal ganglion cells and nerve fibre layer can be reflected by a reduction in macular and central retinal thickness. NAION eyes were shown to have maculae that were thinner and smaller in volume than those of uninvolved eyes.…”
Section: Introductionmentioning
confidence: 99%
“…NAION eyes were shown to have maculae that were thinner and smaller in volume than those of uninvolved eyes. 10 Recently, in addition to macular thickness map, a posterior pole scan has been introduced in the Spectralis SD-OCT (Heidelberg Engineering, Heidelberg, Germany), which displays the retinal thickness over the entire posterior pole (30 Â 25 OCT volume scan). Of particular interest, therefore, is whether posterior pole retinal thickness (PPRT) correlates well with visual field (VF) thresholds (differential light sensitivity).…”
Section: Introductionmentioning
confidence: 99%